BEST FOR CAN – bringing empirically supported treatments to children and adolescents after child abuse and neglect: study protocol. Issue 1 (31st December 2020) - Rosner, Rita; Barke, Antonia; Albrecht, Björn; Christiansen, Hanna; Ebert, David Daniel; Lechner-Meichsner, Franziska; Muche, Rainer; Zarski, Anna-Carlotta; Steil, Regina
ABSTRACT: Background: Despite a large body of evidence demonstrating the effectiveness of psychotherapy for posttraumatic stress for children and adolescents, the adoption of empirically supported treatments (ESTs) in routine care is low. Objective: This implementation study aims to evaluate the dissemination of Trauma-Focused Cognitive Behavioural Therapy (TF-CBT) for children and adolescents with posttraumatic stress symptoms (PTSS) after child abuse and neglect (CAN) with a focus on supervision. Method: In a cluster-randomized controlled trial, the study will evaluate the implementation of TF-CBT focussing on the training of therapists including the provision of supervision. The effectiveness of specialized trauma-focused supervision will be compared to supervision as usual with respect to the successful implementation of TF-CBT for youths with PTSS administered by psychotherapists with different levels of professional experience. The primary outcome is whether the patient receives a treatment with sufficient adherence to the TF-CBT manual. The unit of randomization will be the therapists. The main outcome will be analysed using multilevel logistic regressions. Secondary outcomes will concern further patient-related (reduction of PTSS and depressive symptoms) and therapist-related (professional quality of life) variables. Additional exploratory analyses are planned. Discussion: Since the trial is designed as an implementation study, it permits naturalistic referrals to the participating therapists by patients, caregivers, child and youth welfare agencies and paediatricians. The strict primary outcome will help evaluating the role of model-based supervision in the implementation process. The explorative outcomes will evaluate whether implementation success translates into better patient outcomes. We expect that the dissemination measures will lead to a successful implementation of TF-CBT and promote sustainable structures in routine care that will remain in place after study completion and offer access to ESTs for future children and youths with a history of CAN. Abstract : HIGHLIGHTS: Protocol for a study that investigates the implementation oftrauma-focused cognitive behavioural therapy for children and adolescents with posttraumatic stress symptoms following abuse. The study examines the role of trauma-focused supervision in providing adherent therapy and reducing patients' symptoms.